2021
DOI: 10.1530/eje-21-0239
|View full text |Cite
|
Sign up to set email alerts
|

More than a decade of real-world experience of pegvisomant for acromegaly: ACROSTUDY

Abstract: Objective: To report the final long-term safety and efficacy analyses of patients with acromegaly treated with pegvisomant from the ACROSTUDY. Design: Global (15 countries), multicentre, non-interventional study (2004-2017). Methods: The complete ACROSTUDY cohort comprised patients with acromegaly, who were being treated with pegvisomant (PEGV) prior to the study or at enrolment. Main endpoints were long-term safety (comorbidities, adverse events [AEs], pituitary tumour volumes, liver tests) and efficacy (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
14

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 47 publications
1
32
0
14
Order By: Relevance
“…Despite our study was not being designed to provide data of efficacy of second line therapies, we found that at the follow-up last visit, the control of acromegaly was reached in 22 patients treated with m-Peg-V (66.7%), in 22 patients treated with c-Peg-V (63.9%) and in 25 patients treated with Pasireotide Lar (74.2%). These data are superimposable to those observed in previous series, as the reaching of acromegaly control is reported from 64% to 97% of patients treated with Peg-V in long term follow-up [24][25][26][27][28][29][30][31][32][33][34][35]. This magnitude in the percentage of patients who reached the control of acromegaly by second line therapies may be justified by the different study design (such as clinical trials, randomized or real life studies) and from the dosage of therapies.…”
Section: Discussionsupporting
confidence: 63%
“…Despite our study was not being designed to provide data of efficacy of second line therapies, we found that at the follow-up last visit, the control of acromegaly was reached in 22 patients treated with m-Peg-V (66.7%), in 22 patients treated with c-Peg-V (63.9%) and in 25 patients treated with Pasireotide Lar (74.2%). These data are superimposable to those observed in previous series, as the reaching of acromegaly control is reported from 64% to 97% of patients treated with Peg-V in long term follow-up [24][25][26][27][28][29][30][31][32][33][34][35]. This magnitude in the percentage of patients who reached the control of acromegaly by second line therapies may be justified by the different study design (such as clinical trials, randomized or real life studies) and from the dosage of therapies.…”
Section: Discussionsupporting
confidence: 63%
“…The consensus statements ( 4 ) recommend a combination of first-generation SRL and PEGV in patients who remain uncontrolled with first-generation SRL and with impaired glucose tolerance and tumor concern. In contrast to the consensus statements, we recommend first-generation SRL and PEGV combination therapy as the second-line treatment of choice in nonresponders to first-generation SRL because it can lead to IGF-1 normalization in most patients ( 22 , 23 ). Although PEGV monotherapy does not reduce tumor size, combination therapy has the potential advantage that it may result in tumor size control or even tumor shrinkage in most patients ( 22 , 24 ).…”
Section: Introductionmentioning
confidence: 90%
“…The present investigation is based on the complete analysis set of ACROSTUDY, including data from 15 countries, collected between 2004 and December 2017, when ACROSTUDY was terminated [ 19 ]. Since some nations had enrolled a limited number of patients, we focused the analysis to data from the six top-recruiter countries, i.e., Germany, Italy, France, USA, Spain and the Netherlands.…”
Section: Methodsmentioning
confidence: 99%